2019
DOI: 10.3390/jmse7090293
|View full text |Cite
|
Sign up to set email alerts
|

Depth Selection and In Situ Validation for Offshore Mussel Aquaculture in Northeast United States Federal Waters

Abstract: As mariculture progresses offshore in the US Exclusive Economic Zone, technical and ecological challenges need to be overcome, such as the choice of suitable sites that favor the production of target species. The offshore culture of blue mussels, Mytilus edulis, is performed with submerged longlines and mussels need to withstand more motion than on coastal sites. Temperature affects the ability of the byssus to adhere to farming rope, while chlorophyll concentration provides an estimation of food availability.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 90 publications
0
8
0
Order By: Relevance
“…As an experimental study on giant scallops (Placopecten magellanicus, G. 1791) recruitment [60] demonstrated an interaction effect of thermocline and turbulence on the settlement success, we think the depth in BP may have impacted the recruitment success of mussels on collectors. Several field studies confirmed that blue mussel settlement on artificial collectors is influenced by the presence of a thermocline and depth [13,61,62]. However, we have no indication that collectors' depth is an important driving factor for spat supply differentiation between lagoon and offshore sites in this area.…”
Section: Spat Supply Performancementioning
confidence: 50%
See 1 more Smart Citation
“…As an experimental study on giant scallops (Placopecten magellanicus, G. 1791) recruitment [60] demonstrated an interaction effect of thermocline and turbulence on the settlement success, we think the depth in BP may have impacted the recruitment success of mussels on collectors. Several field studies confirmed that blue mussel settlement on artificial collectors is influenced by the presence of a thermocline and depth [13,61,62]. However, we have no indication that collectors' depth is an important driving factor for spat supply differentiation between lagoon and offshore sites in this area.…”
Section: Spat Supply Performancementioning
confidence: 50%
“…However, nearshore bivalve culture is severely constrained by space limitation and user conflicts [8,9], climate change and fluctuating environmental conditions [6,10], carrying capacity limits or other environmental concerns [4,11], and the need for improving mussel performance and productivity [8,12]. On the basis of several pilot projects conducted in different countries over more than a decade, the establishment of offshore suspended long-line mussel farms has been shown to be promising [4,[8][9][10]13] in areas like the Îles-de-la-Madeleine Archipelago (Gulf of St. Lawrence, Québec, Canada) [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…For example, a precautionary “early harvesting” or the moving of the mussel cultivation off‐the‐coast or offshore could be the best practice to adopt. The last two options are currently considered promising in mussel aquaculture to reduce the risk due to changing environment (Mizuta & Wikfors 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Production carrying capacity was reached or even exceeded in several inshore areas (Smaal & van Duren, 2019). The possibility of offshore culture is now explored in many areas around the world, e.g., the U.S. east coast, Tasmania, Great Britain, and Belgium (Mizuta et al, 2019;Villalba et al, 2022).…”
Section: Bivalves and Other Herbivoresmentioning
confidence: 99%